Evaluation of carotenoids and reactive oxygen species in human skin after UV irradiation: a critical comparison between in vivo and ex vivo investigations. Issue 3 (March 2015) - Meinke, Martina C.; Müller, Robert; Bechtel, Anne; Haag, Stefan F.; Darvin, Maxim E.; Lohan, Silke B.; Ismaeel, Fakher; Lademann, Jürgen
Abstract UV irradiation is one of the most harmful exogenous factors for the human skin. In addition to the development of erythema, free radicals, that is reactive oxygen species (ROS), are induced under its influence and promote the development of oxidative stress in the skin. Several techniques are available for determining the effect of UV irradiation. Resonance Raman spectroscopy (RRS) measures the reduction of the carotenoid concentration, while electron paramagnetic resonance (EPR) spectroscopy enables the analysis of the production of free radicals. Depending on the method, the skin parameters are analysed in vivo or ex vivo. This study provides a critical comparison between in vivo and ex vivo investigations on the ROS formation and carotenoid depletion caused by UV irradiation in human skin. The oxygen content of tissue was also determined. It was shown that the antioxidant status measured in the skin samples in vivo and ex vivo was different. The depletion in the carotenoid concentration in vivo exceeded the value determined ex vivo by a factor of about 1.5, and the radical formation after UV irradiation was significantly greater in vivo by a factor of 3.5 than that measured in excised human skin, which can be explained by the lack of oxygen ex vivo.